Ripening associated antioxidant and phytochemical changes in mango (Mangifera indica) cultivar Dusehri - Aniqa; Zarrin Fatima Rizvi (Scientific Reports)
Abstract The phytochemical fingerprinting that add to the nutritional and nutraceutical value of the fruits during the ripening stages is beneficial for human consumption. Therefore, ripening-dependent changes in phytochemical content and antioxidant activities of mango (Mangifera indica L.) cultivar Dusehri at various ripening stages were evaluated. Bioassays for phenolic content, flavonoid content, antioxidant activities, and UHPLC/MS for phytochemical profiling was performed at five ripening stages (RSI-RSV). Total phenolic contents significantly increased from 4.25 to 13.08 µg GAE/mg extract upto stage III and non-significant decrease was observed thereafter. Flavonoid contents varied between 1.16 and 1.23 µg QE/mg extract. DPPH based free radical scavenging activity increased (41.07–52.33%) from stage I to stage V while FRSP based analysis showed decrease (53.01–27.61 µg TE/mg extract) in activity from stage I to stage V. Total antioxidant capacity and total reducing power potential of pulp extract gradually increased towards mango ripening stages. A non-significant change in amylase inhibition was observed from stage I to stage III that significantly dropped in stage IV and V. UHPLC analysis depicted that aconitic, methylisocitric, 2,4,6-Hydroxy benzoic acid and beta glucogallin, poly phenols, 1-Methylxanthine, 3-Furicacid, Heptenoic acid and many others are present at different ripening stages of dusehri mango. PCA analysis and hierarchal analysis show Stage I & II clustering while stages III-V make separate cluster. These phytochemiclas are responsible for many health benefits. The study concludes that dusehri mango have significant antioxidative capacity that are due to diverse phytochemicals.